ASSESSING THE IMPACT OF LEVEL CROSSINGS ON VEHICLE EMISSIONS FOR SUSTAINABLE URBAN TRANSPORTATION - Mira Lestira Hariani; Yackob` Astor; Ikhlas Maddinah Pradana (Jurnal Infrastruktur, 2026)
Level crossings are a persistent source of traffic congestion and vehicular emissions in many urban areas, particularly in mid-sized cities where road and rail networks intersect at grade. This study investigates the impact of level crossing operations on vehicle CO₂ emissions by analyzing traffic delays caused by train movements at nine crossings in Cirebon City, Indonesia. Using field observations, four traffic-related variables were collected: train frequency (crossings/day), average waiting time (seconds), queue length (meters), and idle vehicle count (vehicles/day). Emissions were estimated using the IPCC Tier 1 methodology, and a multiple linear regression model was developed to assess the relationship between traffic conditions and daily CO₂ emissions. The results show that train frequency and idle vehicle count are statistically significant predictors of emissions, with each additional train and idle vehicle contributing substantially to total CO₂ output. While waiting time and queue length were less significant, their influence was observed to be moderated by vehicle type and traffic density. The regression model explains 99.6% of the variance in emissions (Adjusted R² = 0.996), underscoring the strength of the identified predictors. This study highlights the need for localized emission mitigation strategies, such as optimizing train schedules, improving traffic flow near crossings, and accounting for vehicle composition in emission control policies. The methodology and findings provide a practical framework for traffic-environmental assessments in similar urban settings.